A Call for a More Measured Approach to Reporting and Interpreting PISA Results. (May 2016) - Rutkowski, Leslie; Rutkowski, David
In the current article, we consider the influential position of the Programme for International Student Assessment (PISA) and discuss several methodological areas that demonstrate the need for caution when using and interpreting PISA results. We motivate our argument by briefly describing the program's increased influence in educational policy over time. Subsequently, we describe the methodological areas of interest, including sampling participants, the achievement estimation model, and measuring trends. We also offer our perspectives on how the Organisation for Economic Co-operation and Development might productively and more clearly communicate PISA's limitations.